2022
DOI: 10.1177/17479541221075734
|View full text |Cite
|
Sign up to set email alerts
|

The use of player tracking data to analyze defensive play in professional soccer - A scoping review

Abstract: The analysis of tracking data in tactical game analysis is a topic of rising interest, as more detailed insights into performance structure in soccer can be obtained compared to traditional (e.g. notational) analyzes. Compared to the variety and detailed analyzes of offensive play, the number of studies analyzing the defensive play is low. However, in recent years, an increasing number of studies investigating defensive play have been published, so it seems useful to provide an overview of the current state of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Another investigation revealed that midfielders (central, wide, or offensive) play more passes in a 4-4-2 formation, than midfielders in a 4-2-3-1 formation. 21 Previous reviews have already looked at the match performance of soccer players from a variety of perspectives 11,[22][23][24][25] . However, the current body of literature is characterized by heterogeneous methodological approaches, and an overview that summarizes the way tactical formation affects soccer match performance of a team and a positional level does not exist.…”
Section: Introductionmentioning
confidence: 99%
“…Another investigation revealed that midfielders (central, wide, or offensive) play more passes in a 4-4-2 formation, than midfielders in a 4-2-3-1 formation. 21 Previous reviews have already looked at the match performance of soccer players from a variety of perspectives 11,[22][23][24][25] . However, the current body of literature is characterized by heterogeneous methodological approaches, and an overview that summarizes the way tactical formation affects soccer match performance of a team and a positional level does not exist.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since computer technology and science allowed researchers to deal with larger data sets, the construct of the tactical soccer performance received increasing attention ( Sarmento et al, 2018 ). Particularly, current reviews highlight the offensive and defensive tactical performance of single players, groups, and whole teams, thus pointing to the great opportunities in-game analysis research ( Lepschy et al, 2018 ; Goes et al, 2020 ; Forcher et al, 2022a ). Similarly, the interest in the influence of tactical factors on soccer performance has also increased recently ( Modric et al, 2020 ; Vilamitjana et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the prevalent intention from this playing position is to score goals, they usually seem to focus more on the surrounding information (e.g., space between defenders, distance to the target, goal location) [ 51 ] and engage in more individual situations such 1vs1 to create space [ 20 ]. However, at modern football where there seems to be an emergent trend to defend more compact and with a high number of defenders [ 52 ], which may model the attacker’s role towards deceiving the opponents’ by moving to other areas or holding the ball until receiving pressure to then be able to find a free man. As consequence it may contribute towards longer ball possessions, while shorter ball possessions may be characterized by more individual actions.…”
Section: Discussionmentioning
confidence: 99%